Animal Breeding Considerations for Improved Animal Performance in Hot Environments - J. W. Fuquay (Journal of Agricultural and Marine Sciences, 1996)
A variety of options are available for improved performance including altering genotype with genetic improvement of indigenous breeds through selective breeding; upgrading through crossbreeding of indigenous females with semen from genetically superior exotic males with a possible goal of developing a new breed; and introduction of new breeds through transfer of embryos from genetically superior exotic breeds into indigenous females or importation of exotic animals of the desired breeding. Each option has its advantages and disadvantages. The most rapid gains mightbe possible new environment can be a problem.  In the interest of adaptation and survival, systems that utilize the maternal influences of indigenous females are advantageous. In consideration of this maternal influences along with rate of improvement and potential for extensive improvement, both crossbreeding programs that use semen from genetically superior exotic males and those that involve transfer of genetically superior embryo survival and neonatal survival will affect management of any option chosen for genetic improvement but should be of less concern in programs that utilize indigenous females.